Effect of Botanicals on Fall Armyworm and Predators in Sorghum Ecosystem - sunkara, S. V. L.; Swathi, M.; Madhumathi, T.; Kumar, P. Anil (International Journal of Bio-resource and Stress Management, 2023)
The present field experiment was conducted at Agricultural College Farm, Bapatla during kharif (June-November), 2019 to know the impact of botanicals against fall armyworm, S. frugiperda and their natural enemies (coccinellids, spiders and predatory bugs) in the sorghum ecosystem. Among the botanicals, the highest population reduction of FAW egg masses and larval population was recorded in NSKE @ 5% (71.43 and 60.87%, respectively), green chilli pod extract @ 5% (61.90 and 54.35%, respectively), neem leaf extract @ 5% (69.05 and 45.65%, respectively) and garlic bulb extract @ 5% (52.38 and 54.35%, respectively) treated plots. The botanicals that are used in the experiment were found safe from natural enemies. The maximum population of natural enemies i.e., coccinellids, spiders and predatory bugs was recorded in pongamia leaf extract @ 5% (0.16, 0.22 and 0.10 plant-1, respectively) whereas, the least was observed in emamectin benzoate 5 SG @ 11 g a.i. ha-1 (0.02, 0.02 and 0.01 plant-1 respectively) treated plots. The emamectin benzoate 5 SG @ 11 g a.i. ha-1 presented an adverse effect on natural enemies whereas no or few natural enemies were observed compared to botanical extracts. Therefore, it is recommended that spraying of botanicals has to be done four times at weekly intervals to keep FAW populations below economic injury level until crop maturity and these treatments were also found safe to natural enemies of FAW.